2017
DOI: 10.1128/jvi.02101-16
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Intestinal Replication of an Enteric Virus

Abstract: Coxsackievirus is an enteric virus that initiates infection in the gastrointestinal tract before disseminating to peripheral tissues to cause disease, but intestinal factors that influence viral replication are understudied. Furthermore, a sex bias for severe sequelae from coxsackievirus infections has been observed in humans. While mouse models mimicking human pathogenesis have been well characterized, many of these experiments use intraperitoneal injection of coxsackievirus to infect mice, bypassing the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 44 publications
9
68
0
Order By: Relevance
“…These data suggest that treatment with ampicillin and vancomycin does not alter poliovirus replication in the intestine. However, high fecal titers are not always indicative of poliovirus replication in the intestine (9, 20). Input inoculum virus can be shed for a few days following infection and confound interpretation of viral titer data, particularly during antibiotic treatment due to reduced peristalsis (9, 20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that treatment with ampicillin and vancomycin does not alter poliovirus replication in the intestine. However, high fecal titers are not always indicative of poliovirus replication in the intestine (9, 20). Input inoculum virus can be shed for a few days following infection and confound interpretation of viral titer data, particularly during antibiotic treatment due to reduced peristalsis (9, 20).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we established an oral inoculation model for CVB3 to study viral replication within the gastrointestinal tract (20, 21), and here we examined whether bacteria influence coxsackievirus infection. Similar to our observations with poliovirus (9), we found that intestinal bacteria enhance CVB3 fecal shedding and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Upon disease onset mice were euthanized by isoflurane followed by cervical dislocation. Male mice were used throughout, since CVB3 has a sex-dependent enhancement of replication and lethality (7).…”
Section: Methodsmentioning
confidence: 99%
“…CVB3 is spread through the fecal-oral route and has been associated with a wide range of diseases due to systemic viral dissemination, including gastrointestinal distress, type 1 diabetes, myocarditis, aseptic meningitis, cardiac arrhythmias, and death (1)(2)(3)(4)(5). Mouse models of CVB3 infection and pathogenesis have used a variety of inoculation routes, including the natural oral route of infection (6,7), or intraperitoneal (IP) injection, which bypasses the intestinal tract and induces systemic infection of a variety of tissues (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Immune competent mice are orally susceptible to CVB3 infection, but do not succumb to disease. Immune deficient mice lacking the interferon alpha/beta receptor ( Ifnar-/- ) support high levels of viral replication and succumb to disease, providing a more tractable model to study infection with enteroviruses by the natural oral route (1417).…”
Section: Introductionmentioning
confidence: 99%